Ministry and Mission of the Eastern Orthodox Churches in their Work with Children-at-Risk. (July 2016) - Kozhuharov, Valentin
The article discusses the work of the Orthodox Christian churches (mostly the churches in Eastern Europe) with children and especially children-at-risk. This work is new for these churches and is not yet theologically grounded or systematically organized. Observing the various activities of Orthodox Christians with children-at-risk, questions are raised, such as: is this missionary work, or is it ministry, or is it a task fulfilled by individuals and not by the Church at large? These questions are explored, yet readers are left to make their own conclusions. What becomes evident is the necessity for the Orthodox churches to cooperate with other Christian churches and organizations that are engaged in work with children, and particularly those at-risk, so that all learn from each other and continue their ministry with children in more innovative and successful ways, for the glory of God and the salvation of people, especially the 'little ones'.